Meta-analysis of the efficacy and adverse drug reactions of adrenergic alpha-antagonists in treating children with ureteral calculi - Sun, Kai; Zhang, Peizhi; Sun, Yanning; Wang, Qingliang; Xia, Qinghua (Frontiers in Pediatrics, 2023)
This meta-analysis investigated the efficacy and adverse drug reactions (ADRs) of three different adrenergic alpha-antagonists during the treatment of pediatric ureteral stones. Studies were retrieved from MEDLINE, EMBASE, and the Cochrane Controlled Trial Registry until January 2022. We identified 7 articles, including six RCTs and one cohort study. 610 children received either adrenergic alpha-antagonists or placebo. The results confirmed that the three different adrenergic alpha-antagonists could significantly increase the ureteral calculi expulsive rate and shorten the ureteral calculi expulsive time, regardless of the size of the stone “<5mm” or “5-10mm”. Subgroup analysis suggested that all three adrenergic alpha-antagonists increased the ureteral calculi expulsive rate. Tamsulosin and silodosin also have the effect of shortening ureteral calculi expulsive time, while doxazosin has an insignificant effect on ureteral calculi expulsive time. Besides, tamsulosin and silodosin obviously reduced the number of pain episodes caused by ureteral calculi in children. We analyzed the treatment-emergent adverse events (TEAEs) caused by the treatment of three different adrenergic alpha-antagonists to explore their ADRs. The probability of ADRs was increased after treatment with adrenergic alpha-antagonists. Further subgroup analysis revealed the application of tamsulosin was positively correlated with ADRs in children with ureteral calculi, while the application of doxazosin and silodosin had no statistically significant effect on the probability of TEAEs. In a conclusion, this article systematically analyzed the efficacy and ADRs of three different adrenergic alpha-antagonists, and provided reference and guidance for the application of adrenergic alpha-antagonists to treat children ureteral calculi.